A Robust Multi Carrier Frequency Domain Equalization With Proper Channel Estimation - Upadhyay, JP; Mishra, Rakesh; Khan, Mohsin (International Journal of Computer Sciences and Engineering, 2025)
This work deals with the channel estimation and channel equalization for OFDM system. In present scenario every communication system demands high data rate wireless access and larger bandwidth is. This is a challenging task to develop such wireless communication system. The major challenge in the OFDM system is to achieve better channel estimation and channel equalization with lower values of BER (Bit Error Rate) and MSE (Mean Square Error). In this work a low complexity modified iterative linear minimum mean square error (MI -LMMSE) channel estimation algorithm with modified iterative NLMS (MI-NLMS) channel equalization algorithm integrated with CC-OFDM system is proposed.